Mutational signatures in esophageal adenocarcinoma define etiologically distinct subgroups with therapeutic relevance - Secrier, Maria; Li, Xiaodun; de Silva, Nadeera; Eldridge, Matthew D.; Contino, Gianmarco; Bornschein, Jan; MacRae, Shona; Grehan, Nicola; O'Donovan, Maria; Miremadi, Ahmad; Yang, Tsun-Po; Bower, Lawrence; et al. (Nature Publishing Group, 2016)
Esophageal adenocarcinoma (EAC) has a poor outcome, and targeted therapy trials have thus far been disappointing owing to a lack of robust stratification methods. Whole-genome sequencing (WGS) analysis of 129 cases demonstrated that this is a heterogeneous cancer dominated by copy number alterations with frequent large-scale rearrangements. Co-amplification of receptor tyrosine kinases (RTKs) and/or downstream mitogenic activation is almost ubiquitous; thus tailored combination RTK inhibitor (RTKi) therapy might be required, as we demonstrate in vitro. However, mutational signatures showed three distinct molecular subtypes with potential therapeutic relevance, which we verified in an independent cohort (n = 87): (i) enrichment for BRCA signature with prevalent defects in the homologous recombination pathway; (ii) dominant T>G mutational pattern associated with a high mutational load and neoantigen burden; and (iii) C>A/T mutational pattern with evidence of an aging imprint. These subtypes could be ascertained using a clinically applicable sequencing strategy (low coverage) as a basis for therapy selection.